Driving voluntary reduction of single-use plastic consumption: Capability, opportunity, and motivation - Daisy Lee; Calvin Wan; Sebastian Isbanner; Sharyn Rundle-Thiele; Yi-Ning Fung (Sustainable Futures, 2025)
The excessive use of single-use plastic (SUP), especially SUP tableware, has caused a global plastic waste crisis. Understanding the factors that drive consumers to reduce SUP tableware usage is essential for addressing this issue. Current studies often use simplistic models that fail to capture the complexity of human behavior in reducing SUP, indicating a need for more comprehensive approaches. Grounded in the robust COM-B model and the Theoretical Domains Framework (TDF), this study aims to understand the factors influencing individuals' behavior to reduce SUP tableware. These frameworks offer a solid basis for our research, viewing complex SUP consumption behavior as an interplay of capability (psychological and physical), opportunity (social and environmental support), motivation (people’s thinking and feeling), and outcome behavior. Two online surveys were administered to 354 (Study 1) and 644 (Study 2) Chinese participants. Results showed that capability and opportunity are associated with SUP tableware reduction behavior, fully mediated by motivation. The model explains 70 % of motivation in SUP tableware reduction. Motivation predicts approximately 48 % of actual SUP tableware reduction behavior. Capability, opportunity, and motivation are higher-order constructs measured by lower-order constructs. Capability is predicted by action control, action planning, action skills, decision-making, and habits. Behavioral Opportunity is associated with social norms, social support, and environment. Motivation is affected by identity, reinforcement, goals, and self-efficacy. Finally, theoretical and practical contributions inspiring more consumers to protect our environment were discussed.